2022
DOI: 10.3390/cancers14040900
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Silver(I) Complexes with Metronidazole Drug Reveal Antimicrobial Properties and Antitumor Activity against Human Hepatoma and Colorectal Adenocarcinoma Cells

Abstract: Silver salts and azole derivatives are well known for their antimicrobial properties. Recent evidence has demonstrated also their cytotoxic and genotoxic potential toward both normal and cancer cells. Still, little is known about the action of complexes of azoles with silver(I) salts. Thus, the goal of the study was to compare the chemical, cytotoxic and antimicrobial properties of metronidazole complexes with silver(I) nitrate and silver(I) sulfate to metronidazole and pure silver(I) salts. We synthetized a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“… 39 Several studies indicated that silver(I) complexes show better cytotoxicity against tumor cells including myeloid leukemia cells K562, MCF-7 breast cancer, colorectal Adenocarcinoma Cells Caco-2 cells, and human Hepatoma HepG2. 40 , 41 Our study suggested that gingerol-metal complex-Ag has the potential to be developed as chemotherapeutic agent against colorectal cancers.…”
Section: Resultsmentioning
confidence: 77%
“… 39 Several studies indicated that silver(I) complexes show better cytotoxicity against tumor cells including myeloid leukemia cells K562, MCF-7 breast cancer, colorectal Adenocarcinoma Cells Caco-2 cells, and human Hepatoma HepG2. 40 , 41 Our study suggested that gingerol-metal complex-Ag has the potential to be developed as chemotherapeutic agent against colorectal cancers.…”
Section: Resultsmentioning
confidence: 77%
“…The antimicrobial potential of silver(I) complexes is well known, and recent studies have also demonstrated their cytotoxic and genotoxic potential toward normal and cancer cells. 47,48 In comparison to simple silver(I) salt, it was found that silver(I) complexes with organic-based ligands exhibit more varied chemical properties. 47 Moreover, the use of simple silver(I) salts has been limited since they undergo fast dissociation, leading to the precipitation of AgCl under physiological conditions, a process that prevents the antimicrobial action of silver(I) ion in accordance with the pathways previously described.…”
Section: Electrochemical Behaviormentioning
confidence: 99%
“…47,48 In comparison to simple silver(I) salt, it was found that silver(I) complexes with organic-based ligands exhibit more varied chemical properties. 47 Moreover, the use of simple silver(I) salts has been limited since they undergo fast dissociation, leading to the precipitation of AgCl under physiological conditions, a process that prevents the antimicrobial action of silver(I) ion in accordance with the pathways previously described. 34 To determine the influence of the coordinated silver(I) ion on the antimicrobial activity of complexes 1-3, the biological properties of these complexes were compared with those of the corresponding antifungal azoles (Table 2).…”
Section: Electrochemical Behaviormentioning
confidence: 99%
“…Moreover, silver(I) complexes with metronidazole (MTZ) and miconazole (MCZ) have demonstrated more diverse biochemical properties compared to free ligands and silver(I) salts alone [18][19][20][21][22][23]. Miconazole (Figure 1) is a broad-spectrum azole antifungal with some additional activity against Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important consideration when applying metronidazole composites with silver nanoparticles as antibacterials, as they do not demonstrate toxic side effects toward mammalian cells and tissues [36]. were synthetized by our group and further studied [18][19][20][21][22][23], along with their potential cytostatic activity in A375 human skin cancer cells and normal BJ cells. In addition, to comprehensively assess their potential as anticancer agents, this study also evaluates their impact on blood coagulation and red blood cell hemolysis.…”
Section: Introductionmentioning
confidence: 99%